PENGARUH PENERAPAN MODEL COOPERATIVE LEARNING TEKNIK TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI IIS 1 SMAN 16 PADANG - Melisa, Mutia - (Pendidikan Matematika, 2014)
This research is motivated by low learning achievement math of students andmany students are not sure with their answer and prefer have a copy from theirfriend. The objective of this study to know if applying the model of CooperativeLearning techniques Two stay Two Stray effect on students learning achievementof Mathematic students grade X1 IIS 1 SMAN 16 Padang and how studentslearning attitude after using the model of Cooperative Learning techniques Twostay Two Stray. Type of this research is pre-experiment with scheme of researchPre-test and Post-test group. The hypothesis result using t test showed thathypothesis was accepted with value of thitung is 11.92 and the value of studentsâattitude based on the result of the 1st observation is 3.13 with criteria B (good)and at the 2nd meeting with criteria SB (very good). It can be concluded there isthe effect of applying a model of Cooperative Learning techniques Two stay TwoStray to the mathematics learning achievement and attitudes of students at classX1 IIS I SMAN 16 Padang.